Social control: knowledge and attitude of professionals in the Academia da Cidade Program - Cícero Adriano Melo Figueirêdo; Bruno César Rodrigues da Silva; Amanda Emmanuelly de Melo Tavares Albuquerque; Mateus Gustavo Brainer; Sulamita Emy Tavares de Oliveira Mendonça Soares; Emmanuelly Correia de Lemos (Revista Brasileira de Atividade Física e Saúde)
The aim of this study was to describe the knowledge and attitude of professionals in the Academia da Cidade Program (ACP) in relation to social control. A cross-sectional, descriptive study with a quantitative and qualitative approach was carried out, using a self-administered questionnaire. The data were tabulated using the EpiData Entry v program. 3.1. For the analysis of the quantitative data, SPSS software version 10.0 was used, results were presented in relative and absolute frequencies. For qualitative analysis, the Content Analysis proposed by Bardin was used. 104 professionals participated, who understand social control with "Participation of users, workers and managers in the planning, formulation, evaluation and inspection of health actions, plans, projects and programs". The majority (61.5%) participated in health conferences, considered this participation as very important (62.5%). Moreover, the great majority (81.7%) encouraged users to participate in social control spaces, as well as, valued and reflected (93.3%) on the demands indicated by them. However, more than 90.0% did not participate in health councils and territorial meetings. As a result, it was found that the majority of ACP professionals know social control according to the theoretical framework of the Unified Health System. As for the attitude, they participated in conferences, encouraged users to be participative and valued the claims brought by their routine work in the Program. However, they did not participate in the health councils and the social control spaces within their territory. It is suggested that these findings guide educational and training actions at the municipal and state levels.